Marching students : Chicana and Chicano activism in education, 1968 to the present - Berta-Ávila, Margarita, 1972-; Tijerina Revilla, Anita , 1973-; López Figueroa, Julie, 1969- (University of Nevada Press, 2011)
In 1968 over 10,000 Chicana/o high school students in East Los Angeles walked out of their schools in the first major protest against racism and educational inequality staged by Mexican Americans in the United States. They ignited the Mexican-American civil rights movement, which opened the doors to higher education and equal opportunity in employment for Mexican Americans and other Latinos previously excluded. Marching Students is a collaborative effort by Chicana/o scholars in several fields to place the 1968 walkouts and Chicana and Chicana Civil Rights Movement in historical context, highlighting the contribution of Chicana/o educators, students, and community activists to minority education.